2020
DOI: 10.1016/j.snb.2020.128247
|View full text |Cite
|
Sign up to set email alerts
|

First clinical evaluation of a quartz enhanced photo-acoustic CO sensor for human breath analysis

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Despite the large potential of QEPAS sensors, their reliability in real-life applications have barely been addressed in the literature [ 14 , 30 , 31 , 32 ]. Most experimental demonstrations have been conducted in a laboratory environment using a single gas in an N matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large potential of QEPAS sensors, their reliability in real-life applications have barely been addressed in the literature [ 14 , 30 , 31 , 32 ]. Most experimental demonstrations have been conducted in a laboratory environment using a single gas in an N matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The market for gas sensors was estimated to be 2.23 billion USD in 2020 and is expected to reach 4.49 billion USD in 2028 [ 1 ]. The growing interest in gas sensors is driven by various field of applications, e.g., medicine [ 2 ], air quality [ 3 ], food processing [ 4 ], or security and defense [ 5 ], that address legislative (e.g., EU’s air quality directives), National Ambient Air Quality Standards) and/or individual needs. Sensors commonly used in the market, according to the highest percentage contribution into the gas sensor market income, are electrochemical, semiconductor, and infrared sensors [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, patients are usually resistant to this method because it causes damage to skin tissues and is accompanied by an obvious stinging sensation, and there are unsafe factors that can easily cause infection. Therefore, the development of a noninvasive detection technique has become a hot spot in medical research, and breath analysis, as a new noninvasive detection technique, has been favored by many researchers [2][3][4][5][6][7][8]. Studies have shown that the human breath contains more than 1000 volatile organic compounds (VOCs) [9].…”
Section: Introductionmentioning
confidence: 99%